2021
DOI: 10.30659/jdh.v4i1.13886
|View full text |Cite
|
Sign up to set email alerts
|

The Criminal Sanctions Implementation of Personnel Sexual Violence on Under Age�s Children (Minors)

Abstract: The objectives of this research are: To analyze and explain implementation of criminal sanctions for perpetrators of sexual violence against minors. To analyze and explain constraints and solutions implementation of criminal sanctions for perpetrators of sexual violence against minors. The method used by researchers is a sociological juridical legal approach and the specifications in this study are descriptive. Based on the results of the research that the implementation of criminal sanctions for perpetrators … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
2
0
0
Order By: Relevance
“…Additionally, we found that children from poor families (50%) experienced more violence than those from normal or affluent families. Our findings align with studies by Afandi & Ma'ruf (2021) and Carrera et al (2021), which have shown that children from low-income families are at a greater risk of violence. Furthermore, these studies suggest that parents with low levels of education may be more inclined to use violent disciplinary measures.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Additionally, we found that children from poor families (50%) experienced more violence than those from normal or affluent families. Our findings align with studies by Afandi & Ma'ruf (2021) and Carrera et al (2021), which have shown that children from low-income families are at a greater risk of violence. Furthermore, these studies suggest that parents with low levels of education may be more inclined to use violent disciplinary measures.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, 85.7% reported that their parents blamed them using insulting words and qualities. These findings correspond with studies by Beckmann et al (2021) and Afandi et al (2021), which emphasize that forms of verbal violence by parents against children can include a range of behaviors, such as insults, belittling, criticizing, blaming, and using demeaning language. Verbal violence can also involve threats, intimidation, and coercion.…”
Section: Discussionsupporting
confidence: 89%